Pemahaman Nasionalisme Indonesia di Antara Masyarakat Papua di Kampung Yabanda Distrik Yaffi Kabupaten Keerom - Yan Dirk Wabiser; Yurenius B. Makayan (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
This journal aims to explore the understanding of nationalism among Papuans, particularly in Yabanda Village, Yaffi District, Keerom Regency. Using a qualitative approach, data was collected through interviews and observations. The results revealed that nationalism among Papuans is influenced by various factors, including the history of colonialism, social interaction and economic development. The research also found that while there is love for the Indonesian homeland, there are also feelings of dissatisfaction regarding the marginalization and injustice experienced by Papuans. These findings should provide insights into the dynamics of nationalism in Papua and its contribution to national unity.